2020
DOI: 10.1101/2020.04.21.052712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naïve orangutans (Pongo abelii & Pongo pygmaeus) individually acquire nut-cracking using hammer tools

Abstract: 28Several species of non-human apes have been suggested to rely on copying to acquire some of 29 their behavioural forms. One of the most cited examples -and UN-protected -is nut-cracking 30 in chimpanzees. However, copying might not be the most parsimonious explanation for nut-31 cracking, considering the lack of evidence for spontaneous copying in this species. The zone 32 of latent solutions (ZLS) hypothesis argues instead that the behavioural form of nut-cracking 33 is individually learnt, whilst non-copyi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
(112 reference statements)
1
7
0
Order By: Relevance
“…This effect is most clearly observed in studies in which very closely related subspecies were found to differ in their tool-use abilities (e.g. long-tailed macaques; Luncz et al, 2017;and otters;Ladds, Hoppitt & Boogert, 2017;Bandini et al, 2020a) even when they share the same environment and/or are placed in the same testing conditions. Furthermore, measurements of intelligence (which may be correlated to the ability to use tools; Navarrete et al, 2016) have also been suggested to be heritable in chimpanzees (Hopkins, Russell & Schaeffer, 2014), and dolphin sponging behaviour (in which dolphins use sponges as foraging tools; Krützen et al, 2005), has been suggested to be predicted by genetic relatedness with other spongers in the community (Krützen et al, 2005; although see Sargeant et al (2007) for a contrasting view).…”
Section: Genetic Influencesmentioning
confidence: 88%
“…This effect is most clearly observed in studies in which very closely related subspecies were found to differ in their tool-use abilities (e.g. long-tailed macaques; Luncz et al, 2017;and otters;Ladds, Hoppitt & Boogert, 2017;Bandini et al, 2020a) even when they share the same environment and/or are placed in the same testing conditions. Furthermore, measurements of intelligence (which may be correlated to the ability to use tools; Navarrete et al, 2016) have also been suggested to be heritable in chimpanzees (Hopkins, Russell & Schaeffer, 2014), and dolphin sponging behaviour (in which dolphins use sponges as foraging tools; Krützen et al, 2005), has been suggested to be predicted by genetic relatedness with other spongers in the community (Krützen et al, 2005; although see Sargeant et al (2007) for a contrasting view).…”
Section: Genetic Influencesmentioning
confidence: 88%
“…No observations were made of orangutans spontaneously using the hammers to strike the core in the absence of human demonstrations. Given this spontaneous, untrained expression of lithic percussion by naïve orangutan individuals (see also examples in other orangutan populations Bandini, Grossmann, et al, 2021;and capuchins Westergaard & Suomi, 1994) it is likely that O1 did not acquire the know-how involved in lithic percussion from the demonstrations but instead socially gathered and used information regarding the target (know-where/know-what) of percussion.…”
Section: Discussionmentioning
confidence: 99%
“…were provided with human demonstrations, the observed stone-related behaviours were much rarer and limited to only certain actions (i.e. occasional percussion) that are not outside the spontaneous abilities of naive apes (Bandini, Grossmann, et al, 2021;Motes-Rodrigo et al, 2022). In orangutans, it seems that human demonstrations (provided in an individual setting) are not sufficient for the acquisition of the complete sequence of stone tool making and use when the individuals are not enculturated (Motes-Rodrigo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Reading 3, H&S imply that there are forms that do not need to be copied but are individually reinnovated instead (induced by socially mediated reinnovations) before additional, at least somewhat dissimilar, forms can be individually reinnovated (an "internal ratchet effect" of sorts). 17 This is a theoretical possibility, but is again one that the ZLS approach acknowledges (we call this the "grey zone of cumulative culture"; see Tennie et al (2020b). 18 In Reading 4, H&S allow not only social learning of the types already included in the ZLS account, but additionally allow the copying of know-how (i.e., formcopying.…”
Section: A Comparison Of Approachesmentioning
confidence: 99%
“…The human case logically requires form-copying mechanisms(Tennie et al , 2020a). 17 Or, more generally, where past innovations change the likelihood of future innovations within individuals, and, due to the effects of socially mediated reinnovations, also in affected populations (seeTennie et al 2020b).18 This chapter has been in press since 2017 (which is standard for book chapters). Note that the empirical evidence for this gray zone of cumulative culture is very limited in apes-rendering a "ZLS-only" gambit(Reindl et al 2018;Tennie et al 2020a) still the best overall empirical fit for the available data.19 "[H]abitus includes general problem perceptions and implicit knowledge about specific resources, their qualities and application, timing and pattern of acquisition, pathways, locations, and tools as well as practices of their manufacture, use, maintenance, and discard" (p. 169 in H&S; emphasis added).…”
mentioning
confidence: 99%